Knowledge and Attitudes of Farmer Regarding The Use of Antibiotic and Its Resistance in Broiler Chicken at Aceh Besar Farm - Aulia Malik Fajar; Rastina Rastina; Muhammad Jalalluddin; Ismail Ismail; Muhammad Hanafiah; Teuku Reza Ferasyi (The Faculty of Veterinary Medicine of Syiah Kuala University, 2021)
This study aims to assess farmers' knowledge and attitudes towards the use of antibiotics in broiler chickens in Aceh Besar Farm. The respondents' population was obtained from 13 farmers who were interviewed, and the results obtained were 13 samples with a margin of error of 5%. Data were collected by interview using an open questionnaire that had been validated. The validity test results of farmers' knowledge and attitudes have a value of r 0.5529, which means that they are declared valid. The reliability test results of knowledge and attitudes of animal husbandry have a value of 0.60, so both are declared reliable. Data were analyzed using independent t-test. Based on the interview results, 80% of the farmer respondents in Aceh Besar had good knowledge of the use of antibiotics, 93.33% of respondents gave antibiotics according to clinical symptoms. Farmers' knowledge and attitudes towards the use of antibiotics based on business experience (5 years and ≥ 5 years) showed significantly different results (p0.05). The farmer's knowledge and attitudes towards the use of antibiotics based on the number of broilers raised on the farm showed no significant difference (p0.05). Based on gender and age, farmers' knowledge and attitudes showed no significant difference (p 0.05 in all comparisons). The knowledge and attitudes of 13 farmers were good towards the use and resistance of antibiotics in Aceh Besar District.